The Myth of America's Decline : Politics, Economics, And a Half Century of False Prophecies - Joffe, Josef (New York Liveright Publishing Corporation, 2015)
A provocative and contrarian work-filled with great lessons from history-that challenges the pervasive notion that America is on the decline.
Include Tables, Figure, Notes and Index.
Politics, Economics, And a Half Century of False Prophecies.
Keywords: United States -- Economic history -- Diplomatic relations -- Politics and government